On the Way to Epistemological Anarchism - Jankauskas, Skirmantas (Problemos, 1983)
Basing on a definite example of Paul Feyerabend’s research the outcome of the modem British-American philosophy of science is studied. Its modem trend, the “historical school”, has resulted from the transition to the investigation of the dynamic aspect of science. However, having undiscriminatingly inherited the methods of logical analysis and structural modelling from logical empiricism the representatives of the above trend were confronted with unsolvable problems and arrived at paradoxical conclusions. Disagreement between the methods of research with regard to the object of investigation as well as metaphysical absolutisation of some aspects of research is considered the underlying reason.